Mamfaatkan Limbah Skrap Aluminium Untuk Knalpot Sepeda Motor Vega ZR Tahun 2011 Guna Mengurangi Polusi Udara - Arie Pranata; Ahmad Marabdi Siregar; Budi Dharma; Wawan Septiawan Damanik; Arya Rudi Nasution (Rekayasa Material, Manufaktur dan Energi, 2021)
The number of motorized vehicles increases from year to year, the exhaust gases generated from these motorized vehicles cause air pollution by 70 to 80 percent, so efforts need to be made to control exhaust gas emissions. Considering the danger of exhaust gas emissions, the effort that needs to be made to control and reduce air pollution is the engineering and modification of the exhaust gas lines. Engineering and modification of exhaust gas lines, namely by innovating the exhaust by adding aluminum scrap. Researchers will conduct experiments and manufacture of tools and initial testing on motorized vehicles to see and observe the composition of exhaust gases produced from standard exhausts. The elements to be observed are the CO value, HC value, and CO2 value as comparison data. The tool that will be used to observe and see these elements is the Gas Analyzer. From the results of testing and analysis, data on exhaust emission tests with an average engine speed of 4000 rpm, and with an exhaust pipe temperature of 40 oC to 45 oC, were obtained. After testing the standard exhaust, then testing the modified exhaust and the addition of scrap 60 gr, 70 gr, and 80 gr aluminum obtained the best conclusion to reduce the danger of exhaust emissions from the modified exhaust added 60 gr aluminum scrap and when compared to the exhaust. the standard CO yield fell to 11.7%, HC fell to 4.26%, and CO2 fell to 1.59%.